2010
DOI: 10.1128/jb.00007-10
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Pilin and Nonpilin Protein Constructs byPseudomonas aeruginosa1244

Abstract: PilO is an oligosaccharyl transferase (OTase) that catalyzes the O-glycosylation of Pseudomonas aeruginosa 1244 pilin by adding a single O-antigen repeating unit to the ␤ carbon of the C-terminal residue (a serine). While PilO has an absolute requirement for Ser/Thr at this position, it is unclear if this enzyme must recognize other pilin features. To test this, pilin constructs containing peptide extensions terminating with serine were tested for the ability to support glycosylation. It was found that a 15-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In Gram-negative bacteria, examples of surface-associated glycoproteins include the pilins of P. aeruginosa and Neisseria spp. (29,30), the adhesins TibA and Aida-1 of E. coli (31,32) and HMW1 of Haemophilus influenza (33), and the flagellins of A. avenae and many other pathogenic bacteria (7,34,35). Although the full significance of the glycosylation of these proteins has not been determined, a number of reports have shown that these modifications are involved in virulence and motility.…”
Section: Discussionmentioning
confidence: 99%
“…In Gram-negative bacteria, examples of surface-associated glycoproteins include the pilins of P. aeruginosa and Neisseria spp. (29,30), the adhesins TibA and Aida-1 of E. coli (31,32) and HMW1 of Haemophilus influenza (33), and the flagellins of A. avenae and many other pathogenic bacteria (7,34,35). Although the full significance of the glycosylation of these proteins has not been determined, a number of reports have shown that these modifications are involved in virulence and motility.…”
Section: Discussionmentioning
confidence: 99%
“…Their small size and ability to mediate motility or transduce electrons highlight the potential for their exploitation for industrial purposes, including formation of nanotubes with emergent properties (25,27), movement of nanoscale cargo (410), and powering of bacterial batteries (261). Their ability to tolerate bulky modifications such as sugars (55,73,131,323,405) or peptides (400) makes them amenable to synthetic biology approaches (272) for development of completely novel uses, once a compre-hensive understanding of their functional logic is available. The use of filamentous phages that have T4P-like assembly systems, such as M13, has revolutionized many aspects of molecular biology (406), and the type IV pilins are equally suited to take us in new directions.…”
Section: Discussionmentioning
confidence: 99%
“…The factors determining this remarkable preference for short oligosaccharides remain to be established. The only substrate specificity that could be found for PilO is the presence of a C-terminal serine or threonine residue and the above-mentioned minimum distance from the pilin surface and compatible surface charge (393).…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…Commonalities in glycosylation pathways reduce the arsenal of precursors and enzymes needed and are thus energy saving. Bacteria also need a way to discriminate between these bifurcated biosynthesis pathways and have evolved several solutions to do so: they can express only a subset of the glycoconjugate repertoire (e.g., H. pylori [322]), use downstream enzymes with different specificities (e.g., P. aeruginosa [393]), and have both pathways compete (e.g., the same precursors for LOS, CPS, and N-glycoprotein biosynthesis in C. jejuni [14]), and their expression can be dependent on environmental stimuli (e.g., expression of colonic acid in E. coli [65]). …”
Section: Overlap In Glycoconjugate Biosynthesis Pathwaysmentioning
confidence: 99%